PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL (Studi Kasus pada Perusahaan Sub Sektor Tekstil Dan Garmen Yang Terdaftar di BEI Periode 2012-2016) - Rahmi Rahma Yati; Rika Desiyanti; Yuhelmi Yuhelmi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
This study aims to determine the effect of firm size, sales growth and asset structure on capital structure. In this study, 10 companies in the textile and garment sub-sector are listed on the Indonesia Stock Exchange. The type of data used is secondary data obtained from IDX (Indonesia Stock Exchange) and ICMD (Indonesian Capital Market of Directory) from 2012 to 2016. In this study two categories of variables were used, the first dependent variable was the capital structure. Both independent variables consist of company size, sales growth and asset structure, the process of testing hypotheses is done using panel regression analysis and t-statistical testing. Based on the results of testing the hypothesis it was found that the size of the company and the structure of the assets had no effect on the capital structure of the textile and garment sub-sector companies listed on the Indonesia Stock Exchange, while sales growth had a positive effect on the capital structure of textile and garment sub-sectors in the Indonesia Stock Exchange.